STUDY OF ARACHIDONIC ACID RELEASING STATUS IN DIABETIC RATS TREATED WITH FLAXSEED OIL - Hussein, Jihan; El-khayat, Zakaria; Moify, Mohamed (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Diabetes mellitus increased inflammation through stimulation of arachidonic acid liberation from the cell membranes which is transformed into actively cellular mediators such as thromboxanes, prostaglandins, and leukotrienes. So, this study aimed to investigate the effect of flaxseed oil as a source of omega 3 fatty acids on releasing of arachidonic acid from erythrocyte membrane and also on possible reduction of hyperhomocysteinemia during experimental diabetes. Methods: Forty male albino rats were used in this study and divided into four groups: control, diabetic, flaxseed oil and treated groups. After the experimental period, blood samples were collected to estimate different biochemical parameters in plasma and in the erythrocyte membrane. Results: The data showed the elevation of membrane arachidonic acid along with the elevation of inflammatory and oxidative stress markers in the diabetic group while flaxseed oil supplementation significantly decreased these levels. Conclusion: We concluded that flaxseed oil is a promising supplement during diabetes mellitus due to its powerful effect in reducing arachidonic acid release and inhibition of hyperhomocysteinemia. Keywords: flaxseed oil, Arachidonic acid, Hyperhomocysteinemia, Cell membrane, HPLC